EDUKASI PRINSIP-PRINSIP ERGONOMIS SEBAGAI UPAYA PENCEGAHAN PENYAKIT MUSKULOSKELETAL PADA PERAWAT DI RUANG PERAWATAN INTENSIF - Sartika, Dewi; Rusdi, Ibnu; rusherina, Rusherina (Poltekkes Kemenkes Riau, 2024)
The provision of quality nursing services is determined by the performance of nurses in providing nursing care. The delivery of nursing care has hazards, one of which is ergonomic hazards. Good knowledge of ergonomic principles is essential for nurses therefore nurses have self-awareness, can improve work behavior, and avoid the negative impacts of ergonomic hazards, namely musculoskeletal diseases. This community service activity was carried out on nurses in the intensive care unit at a hospital in Pekanbaru City, which began with a pre-test, education, and post-test. Education was carried out using media as an Education Module consisting of working in a neutral/non-awkward position and posture, reducing excessive loads, reducing excessive repetitive movements, minimizing static positions, minimizing pressure at certain points, and stretching at work. The evaluation results showed an increase in nurses' knowledge after being given education. This activity is known to be effective as an initial solution in improving nurses' understanding of ergonomic principles in providing nursing care which is still lack. It is expected that this educational activity can be carried out on nurses in other clinical settings with more varied methods and media and reinforced with reminders.